The Development of Irish-American Children's Literature (1850-1940) - Ní Choileáin, Méabh Margaret (Trinity College Dublin. School of English. Discipline of English, 2026)
This thesis examines the previously undefined category of Irish-American children's literature, arguing that it played a crucial role in shaping and transmitting ideas of Irish immigrant identity in the US to a young readership between the mid-nineteenth and mid-twentieth centuries. While Irish-American literature has been widely studied, criticism to date has focused almost exclusively on fiction for adults, thus overlooking works written for children. Similarly, critics of American children's literature have overlooked the valuable contribution of Irish immigrant authors to the development of this category. Filling these critical gaps, this thesis recovers and reclassifies children's literature by Mary Anne Sadlier, Fr. John T. Roddan, John McElgun, Mary E. Mannix, Julia C. Walsh, and Padraic Colum. Through a combination of close textual analysis, extensive archival research, and an interview with a descendent of Mary E. Mannix, the thesis demonstrates how Irish-American authors utilised the medium of children's literature to impose particular values on an implied Irish Catholic immigrant child reader. By examining previously overlooked works by Irish-American authors as children's literature, and analysing their engagement with themes of identity, memory, and belonging, this thesis demonstrates how texts for young readers served as crucial sites in which Irish-American identity was constructed, negotiated, and promoted for young people during a critical period in Irish American history.
APPROVED
Keywords: Children's Literature; Irish-American Literature; American Children's Literature; Irish Immigration; Diaspora Studies; Irish-American History